The Role Of Sports Sociology In Social Life, Both At The Individual And Group Levels - Eki Nurhikma; Muhammad Iqbal Rustan; Muh. Adnan Hudain; Yusnadi; Alimin Alwi (Asosiasi Dosen Muda Indonesia, 2025)
Sport is not only understood as a physical activity, but also as a social phenomenon that influences interaction patterns, identity formation, and societal structures. This article aims to analyze the role of the sociology of sport in social life at the individual and group levels. The research uses a descriptive qualitative method through a literature review that examines various academic sources related to the social dynamics in sport practices. The results of the study indicate that at the individual level, sport plays a role in character formation, value socialization, and the development of social and emotional competencies such as discipline, cooperation, and sportsmanship. At the group and community level, sport functions as a medium for social cohesion, forming collective identity, and uniting multicultural societies. However, sport also reflects social inequality, commercialization, gender bias, and power relations as explained through Bourdieu's theoretical perspective. On the other hand, sport has transformative potential as an instrument of empowerment and social development when managed inclusively and equitably. Thus, a sociological understanding of sport is important in formulating sports policies and programs that can strengthen solidarity, foster individual character, and support social development.